PENDUGAAN KANDUNGAN KARBON TEGAKAN AKASIA (Acacia mangium WILD) BERBASIS BEF DI PT INHUTANI III SEBUHUR KALIMANTAN SELATAN - Rina Kanti (Jurnal Hutan Tropis, 2020)
The purpose of this research is to estimate the potential of carbon in the standing of Acacia mangium Willd in Areal PT INHUTANI III Sebuhur of South Kalimantan. The research method of using the ALOS satellite imagery is georectification so that the image position corresponds to the actual position in the field and to see the uniformity of the sample in the NDVI, a descriptive statistical test in the respective NDVI and Klas diameter. Based on the NDVI classification on Citra Alos in 2012, the land area of the wooded area of PT INHUTANI III Sebuhur is 8,183.18 ha. Results Biomass Expansion Factor (BEF) based on 4 klas diameter with polynomial equation Y =-0.0057 X2 + 0.014 x + 1.2623;  R ² = 0.9621 is a klas 5 – 10 diameter in the total of 1,272, Klas, 10 – 15 diameter in total 1.263, klas, in diameter 15 – 20 in total 1.258 and Klas > diameter 20 totalnya1,226. The result of total carbon potential in wooded areas of PT INHUTANI III Sebuhur is 31,497.11 ton/Ha, so the average carbon potential of 3.8489 Ton/Ha. Meanwhile, the potential carbon (ton/ha) based on NDVI 2-7 according to the logarithmic equation Y = 4.7925 ln (X)-2.0321; R ² = 0.9167, with Y is the potential carbon ton/ha and X is NDVI Klas is Klas NDVI 2 1.0462 tons/ha, Klas NDVI 3 of 3.7918 tons/ha, Klas NDVI 4 of 4.7479 tons/ha, Klas NDVI 5 of 4.7213 tons/ha, Klas NDVI 6 of 7.0632 tons/ha, and Klas NDVI 7 of 5.2875 ton/ha.